Molecular Characterization and Stress Tolerance Evaluation of New Allotetraploid Somatic Hybrids Between Carrizo Citrange and Citrus macrophylla W. rootstocks - Ruiz, Marta; Pensabene-Bellavia, Giovanni; Quiñones, Ana; García-Lor, Andrés; Morillon, Raphaël; Ollitrault, Patrick; Primo-Millo, Eduardo; Navarro, Luis; Aleza, Pablo (Frontiers in Plant Science, 2018)
Polyploidy is one of the main forces driving the evolution of plants and provides great advantages for breeding. Somatic hybridization by protoplast fusion is used in citrus breeding programs. This method allows combining the whole parental genomes in a single genotype, adding complementary dominant characters, regardless of parental heterozygosity. It also contributes to surpass limitations imposed by reproductive biology and quickly generate progenies that combine the required traits. Two allotetraploid somatic hybrids recovered from the citrus rootstocks C. macrophylla (CM) and Carrizo citrange (CC) were characterized for morphology, genome composition using molecular markers (SNP, SSR, InDel) and their tolerance to iron chlorosis, salinity and Citrus Tristeza Virus (CTV). Both hybrids combine the whole parental genomes even though the loss of parental alleles was detected in most linkage groups. Mitochondrial genome was inherited from CM in both hybrids, while recombination was observed for chloroplastic genome. Thus, somatic hybrids differ from each other in their genome composition, indicating that losses and rearrangements occurred during the fusion process. Both inherited the tolerance to stem pitting caused by CTV from CC, are tolerant to iron chlorosis like CM and have a higher tolerance to salinity than the sensitive CC. These hybrids have a high potential for areas with calcareous and saline soils where CTV is present, such as the Mediterranean area. The provided knowledge on the effects of somatic hybridization on the genome composition, anatomy and physiology of citrus rootstocks will be key for breeding programs that aim to address current and future needs of citrus industry.